Perspektif Regulasi Kesehatan Internasional dalam Kebijakan Mitigasi Covid-19: Studi Komparatif Antara Indonesia dengan Korea Selatan - Raymond Jonathan; Desak Ayu Gangga Sitha Dewi (Jurnal Hukum Lex Generalis, 2021)
COVID-19 has caused a multidimensional crisis in a global society. Many mitigation policies were made to handle the crisis, especially in South Korea and Indonesia. South Korea’s policies were judged to be effective as the success increased public opinion and participation. As a result, the COVID-19 case’s curve flattened rapidly because of responsive policies and based on international law. Meanwhile, Indonesia continues to show an increase in the case curve because of inconsistent policies and weak law instruments towards emergency health response. As a result, the crisis has more long-term effects and gets worse. It can be concluded that South Korea has more responsive policies and follows more of the International Health Regulation of 2005 compared to Indonesia.